The introduction of rapid diagnostic test for malaria in Mozambique: local appropriation and complementary therapeutics - Sequeira, A. R. (The Australasian Review of African Studies (ARAS), 2015)
In 2008 Mozambique's Ministry of Health (MoH), with the technical and financial support of transnational and international organisations such as United Nations (UN) agencies, USAID (United States Agency for International Development) and INGOs (International Non-Governmental Organisations), amongst others, introduced the Rapid Diagnostic Test (RDT) for malaria to be implemented across the country. This new biomedical technology impacted not just clinical practice, where health workers had to draw blood to be able to diagnose malaria (parasitological confirmation), but interacted with local worldviews and therapeutic practices in ways that needed to be incorporated into therapeutic interventions, notwithstanding patients' overall acceptance of the reliability of RDTs.